O processo de institucionalização da atividade de auditoria da Controladoria Geral do município de Fortaleza: uma análise sob a perspectiva da teoria institucional - Paula, Joelise Collyer Teixeira de (2006)
In the public sector the transparency in the management of the public money is a growing aspiration of population. People are more conscious of their rights and their obligations and this makes the public power to create legal mechanisms of adjustment that discipline the administrative acts of the government, forcing it to behave in a more rational and transparent manner. Aligned to this scenario the controlling joined in the public organs to coordinate the efforts along with the managers to reach an optimized global result, to make them more effectively capable to grant the legality, impersonality, morality, publicity and efficiency, constitutional principles enumerated in article 37 of the Federal Constitution from 1988, with the new composing given by Constitutional Joint nº 19 from June 04, 1998, known as the Administrative Reform of the Joint of 1998. This necessity of a new benchmark to guide the management of the public institutions was intensified with the “Lei de Responsabilidade Fiscal”, LRF/2000. In this new paradigm of public management the “Prefeitura Municipal de Fortaleza” – PMF, instituted through the Law nº 8.608, from December 21, 2001, the “Controladoria Geral do Municipio” (CGM). Parallel to the creation of this new organ many questions referent to the operations of the CGM, that lack investigation, can be answered at the light of an institutional theory, an approach that lacks empirical studies. This work has as a general objective to analyze the roll of institutionalization process of CGM in the auditing activities realized in the ambit of PMF. The theoretical referential developed is divided in two parts, the Controller in the context of the New Economy and the Institutional Approach. The research can be defined, due to the finality, as exploratory and descriptive, and as the tactics, as bibliographic and as field research, been realized by studies of cases, making use of the techniques of interviews with the authors involved in the process of institutionalization of CGM and questionnaires with the auditors of CGM and managers of others municipal organs of Fortaleza, in the period from January to June of 2006. About the nature of the data, the research is configured as qualitative. The results of the research show that the process of institutionalization of the auditing activity of CGM is occurring in a slow and gradual manner, inserted in an uncertain environment, creating many doubts on its users, facing many difficulties in the internal and external ambits.